Lecturer support and self-efficacy on students' off-classroom training effectiveness / Saida Farhanah Sarkam ... [et al.] - Sarkam, Saida Farhanah; Abas, Norlela; Daud, Siti Rohana; Mohamed, Noor Azzura; Wahab, Nurul Aini (Universiti Teknologi MARA, Perlis, 2019)
Off-classroom training is important to sharpen the soft skills of university students. The study discussed the relationship of lecturer support and self-efficacy with training effectiveness of students outside the classroom. The scope of study was 314 agriculture students taking human resource management course. The study applied quantitative research method and underpinned by training engagement theory, which considers both internal and external factors in evaluating training effectiveness. The findings were analyzed using IBM-SPSS v 24 software. The findings showed that both variables significantly influenced training effectiveness, and self-efficacy influenced training effectiveness more than lecturer support. It is concluded that the understanding of the best factor influencing training effectiveness will assist lecturers in designing suitable training programs for the students in the future.